2020
DOI: 10.1039/c9sc06224f
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of mechanochemical synthesis of calcium urea phosphate fertilizer cocrystal reveals highly effective water-based autocatalysis

Abstract: Using the mechanosynthesis of the fertilizer cocrystal calcium urea phosphate as a model, we provide a quantitative investigation of chemical autocatalysis in a mechanochemical reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…volume of added liquid per sample weight (in μL/mg), ‡ between 0.5 and 1.5 μL/mg. These conditions meet the previously established regime of mechanochemical liquid-assisted grinding (LAG) 47 where, as long as η is maintained approximately below 2 μL/mg, the reactions can be accelerated or even catalysed 48 by the presence of a liquid additive, but proceed independent of the relative solubilities of reactants. Due to the absence of solubility limitations typical of reactivity in bulk solvent media, 47 reactions under LAG conditions are generally considered solvent-free.…”
Section: Resultssupporting
confidence: 60%
“…volume of added liquid per sample weight (in μL/mg), ‡ between 0.5 and 1.5 μL/mg. These conditions meet the previously established regime of mechanochemical liquid-assisted grinding (LAG) 47 where, as long as η is maintained approximately below 2 μL/mg, the reactions can be accelerated or even catalysed 48 by the presence of a liquid additive, but proceed independent of the relative solubilities of reactants. Due to the absence of solubility limitations typical of reactivity in bulk solvent media, 47 reactions under LAG conditions are generally considered solvent-free.…”
Section: Resultssupporting
confidence: 60%
“…Additionally, it has been reported that LAG can exert inhibitive or prohibitive effects on the formation of molecular crystals by mechanochemistry [99] . Moreover, in situ released liquid products in mechanochemical transformations have been observed to accelerate chemical reactions, [100] thus indicating the possibility for LAG catalysis (Figure 4c) [101] . Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols [102–105] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…In the case of mechanochemical reactions triggered by pulsed ultrasonication experiments (Figure 6e), synchronous optical measurements by real‐time UV‐vis spectroscopy have enabled to acquire kinetic information to understand the influence of polymer structure and composition on mechanochemical activity (Figure 6e) [216] . As mentioned above, the adoption of in‐process monitoring (GC 11) in the field of mechanochemistry has permitted the elucidation of mechanistic steps in mechanochemical reactions, [205] as well as the correlation of milling parameters on the course of mechanochemical reactions, [217] the observation of short‐lived polymorphic materials, [90] reaction intermediates, [91] and a better understanding of the effect caused by milling additives [100] . However, continuous monitoring of mechanochemical reactions can also lead to safer chemistry and accident prevention (GC 12).…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…[130] Although the mechanism of LAG in mechanosynthesis has been less well studied and the application of LAG is an area in continuous development, further progress would benefit from a better understanding of the role of the liquid-assisted grinding used in the mechanosynthesis process. The methodologies for continuously monitoring milling reactions such as powder X-ray diffraction (PXRD), [131] Raman spectroscopy, [132] or a combination of both techniques [133] leaves much room for researches in terms of the mechanism and expansive application of LAG. It will certainly guide future studies on the use of LAG providing innovative retrosynthetic analysis of drug-like molecules with less environmental impact and high efficiency.…”
Section: Future Prospects For Lag In Pharmaceutical Synthesismentioning
confidence: 99%